Z-scan, Fluorescence and XRD Studies of Thermal Evaporated Zinc-Tetraphenyl Porphyrin Thin Film - Rajesh Kumar P C; Clavian L M; Narayana Rao D (Current Research Progress in Physical Science Vol. 7, 2025)
The Z-Scan technique is an easy and widespread approach to evaluate the nonlinear optical coefficient of materials. The z-scan technique has been used to investigate the third-order nonlinear optical properties of 5,10,15,20 Tetraphenyl 21H,23H-porphine zinc (II) (ZnTPP) thin films with 6 ns laser pulse operating at 532 nm with an average power of 1.94 mW. The thin films of ZnTPP with a thickness of the order of 120 nm are developed by means of the thermal vacuum coating technique. The UV-visible studies show a signature absorption curve identifying the enhancement in the symmetry of the molecule from D2h symmetry to D4h, due to the presence of central Zn metal ion. PXRD pattern demonstrates polycrystalline nature of the material embedded in the amorphous microstructure. The molecular fluorescence spectrum exhibits three emission bands composed of Q (1,0), Q (0,0) and Q (0,1). The ZnTPP thin film exhibits reverse saturation absorption (RSA) and a strong self-defocusing effect. The effective two-photon nonlinear absorption coefficients (\(β\)eff) and nonlinear refractive index (n2) obtained at different input on-axis peak intensities (I0) are of the order of 10-6 to 10-5 m/W and 10-13 to 10-11 m2/W. The decrease in \(β\)eff with the increase in intensity indicates that the observed RSA is due to the excited state absorption (ESA) from the T1 triplet state to the higher triplet state (Tn). The ZnTPP thin film demonstrates strong reverse saturation absorption and self-defocusing effect at nano-second regime. The obtained results suggest that the fabricated ZnTPP thin film is a promising material for nonlinear optical device fabrication.